Grieving in the digital age: using Facebook profile pages to maintain relationships with the deceased - Bouc, Amanda M. (Kansas State University, 2013)
Advancements in technology, particularly the introduction of online social networking sites, have expanded the modes available when handling the death of a loved one. This study examines how individuals use the Facebook profile pages of deceased persons to cope with loss and maintain relationships with them. An extensive content analysis of Facebook profiles of ten deceased individuals was conducted to investigate what the living discuss in their messages to the deceased in the semi-public setting of a Facebook profile page and if this content changes over the course of time. This analysis revealed that messages to the deceased reflect three themes: 1) processing the death, 2) remembering the deceased, and 3) maintaining the relationship. In addition to these dominant themes, the data also indicated that the content of messages shifted over time. Messages that contained the processing of death remained consistent over time, while posts that reflected remembrance of the deceased decreased, and messages that demonstrated relationship maintenance increased with time. This study utilizes the theoretical frameworks of continuing bonds and social information processing to draw implications of these findings. By examining the content written and how messages change over time, this study provides insight into how people cope with loss and maintain relationships with their deceased loved ones in the digital age.
Keywords: Facebook profile; Social information processing theory; Continuing bonds; Deceased; Virtual memorial; Relationships; Communication (0459)